Long-Term Encapsulated Nitrate Supplementation Modulates Rumen Microbial Diversity and Rumen Fermentation to Reduce Methane Emission in Grazing Steers - Granja-Salcedo, Yury Tatiana; Fernandes, Rodolfo Maciel; Araujo, Rafael Canonenco de; Kishi, Luciano Takeshi; Berchielli, Telma Teresinha; Resende, Flávio Dutra de; Berndt, Alexandre; Siqueira, Gustavo Rezende (Frontiers in Microbiology, 2019)
This study investigated the long-term effects (13 months) of encapsulated nitrate supplementation (ENS) on enteric methane emissions, rumen fermentation parameters, ruminal bacteria, and diversity of archaea in grazing beef cattle. We used a total of thirty-two Nellore steers (initial BW of 197 ± 15.3 kg), 12 of which were fitted with rumen cannulas. For thirteen months, the animals were maintained in 12 paddocks and fed a concentrate of ground corn, soybean meals, mineral supplements, and urea (URS) or encapsulated nitrate (EN) containing 70 g of EN/100 kg of BW (corresponding to 47 g NO3−/100 kg BW). Encapsulated nitrate supplementation resulted in similar forage, supplement and total DMI values as URS (P > 0.05), but ENS tended to increase (+48 g/d; P =0.055) average daily weight gain. Daily reductions in methane emissions (-9.54 g or 18.5%) were observed with ENS when expressed as g of CH4/kg of forage dry matter intake (fDMI) (P = 0.037). Lower concentrations of NH3-N and a higher ruminal pH were observed in ENS groups 6 h after supplementation (P < 0.05). Total VFA rumen concentration 6 h (P = 0.009) and 12 h after supplementation with EN resulted in lower acetate concentrations in the rumen (P = 0.041). Steers supplemented with EN had a greater ruminal abundance of Bacteroides, Barnesiella, Lactobacillus, Selenomonas, Veillonella, Succinimonas, Succinivibrio, and Duganella sp. (P < 0.05), but a lower abundance of Methanobrevibacter sp. (P = 0.007). Strong negative correlations were found between daily methane emissions and Proteobacteria, Erysipelotrichaceae, Prevotellaceae, and Roseburia, Kandleria, Selenomonas, Veillonella, and Succinivibrio sp. (P < 0.05) in the rumen of ENS steers. Encapsulated nitrate is a feed additive that persistently affects enteric methane emission in grazing steers, thereby decreasing Methanobrevibacter abundance in the rumen. In addition, ENS can promote fumarate-reducer and lactate-producer bacteria, thereby reducing acetate production during rumen fermentation.